(untitled) (World Bulletin of Social Sciences, 2022)
The research addressed the impact of the climate factor on archaeological sites in Muthanna province, including the city of Al-Warka archaeological, where solar radiation affects the heating of walls to a high degree, and over time the buildings in the sites of the city of Al-Warka affected by solar radiation, as well as the temperature affects the writings and colored inscriptions, which led to the fading of colors and the lack of clarity of writings in the sites and samples of antiquities in the study area, This led to the drying of building materials and thus to break them, and the rains are an important source of moisture and has a great impact on the sites and archaeological buildings in them, as the penetration of rain inside the buildings led to the melting of materials related to the granules of stone blocks, while the speed of the wind affected the carrying of sand with large granules, which led to the carving of the building and changing its features, and the elements of the climate did not affect the archaeological sites only, Rather, the effect is on the samples of bricks and throws